An Analysis of Mathematics Questions of the Tpese Exam According to Cognitive Levels of Timss 2015 - Çalışkan, Nesrin; Kahya, Esra; Temli Durmus, Yeliz (Journal of History Culture and Art Research, 2018)
In this study, it was aimed to compare TEOG Exam Mathematics Questions and TIMSS-2015 8th-grade Mathematics Questions by classifying them according to TIMSS-2015 cognitive domains. For this purpose, document analysis / review method of data collection methods was used. The study is limited to 240 mathematics questions included in TEOG exam and TEOG make-up exam applied to 8th-grade students between 2013 - 2016 and 212 items included in TIMSS-2015 8th grade Math success test. The research data were obtained by the researcher and 3 experts according to the TIMSS-2015 cognitive domain coding scheme. The obtained findings were evaluated by taking their percentages and frequencies. At the result of the study; it is concluded that 42.5% of TEOG and TEOG make-up exam math questions belongs to "Knowing", 45.5% of it belongs to "Practice" and 12% of it belongs to “Reasoning” cognitive domain steps. It is seen that 31% of the items in TIMSS 2015 grade 8 Mathematics achievement test are related to Knowing, 45% of it related to Practice and 24% of it related to “Reasoning” cognitive domain levels. In the TEOG exams, questions that measure high-level thinking skills are less than in the TIMSS exam. The majority of the TEOG questions (88%) constitute questions that measure low-level skills. Moreover, it is seen as a result of testing with chi-square distribution that the cognitive percentages of the TIMSS-2015 mathematics questions and the TEOG exam mathematics questions are significantly different in other words they do not match with each other cognitively. On the other hand, the mathematics questions of the TEOG exam and the mathematics questions of the TEOG make-up exam match with each other cognitively.